The expression of predicative possession : a comparative study of Belarusian and Lithuanian - Mazzitelli, Lidia (Studia typologica ;, 2015)
This book discusses the constructions used in Belarusian and Lithuanian to express predicative Possession. The work is written within a typological frame: the Belarusian and Lithuanian constructions are analyzed in the light of the typology of the possessive predicative constructions proposed by Heine (1997) --